STREAMLINING FINANCIAL MANAGEMENT: THE EVOLUTION OF AUTOMATED ACCOUNTING - Zamira Atabayeva; Habibullaev Abubakir (Web of Journals Publishing, 2023)
This article delves into the legal framework and objectives of accounting, examining prevalent approaches to automate these processes and integrate information technologies. The primary focus is on enhancing the efficiency of management functions across economic sectors. Investigating the nuances of informatization, computerization, and automation in contemporary economic settings is central to this exploration. The article uncovers the distinct advantages of automated accounting when juxtaposed with traditional methodologies while highlighting prevalent computer programs utilized for automated accounting in practical applications.
Keywords: Economy, Control, Accounting, Legal Basis, Information, Automation, Company, Tasks, Information Systems and Technologies, Programs, Computer, Processes.